Sistem Pengelolaan Arsip Pada Dinas Pertanian Dan Ketahanan Pangan Provinsi Jawa Timur - Mega Anggun Aurelita; Susi Ratnawati; Bagus Ananda Kurniawan (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
Archive activities are needed for office activities every day. Difficulty in recovering the required archives will hinder office activities and have a negative impact on the productivity of an organization or company. Existing documents and manuscripts are then stored using a certain system so that they are more organized and easy to find. In archiving activities at the Agriculture and Food Security Office of East Java Province, they still use a manual system, with insufficient HR concern for archive management, and most of the data is not well organized. So, management of records at the Agriculture and Food Security Office of East Java Province is still not fully efficient. Therefore, researchers want to examine how the archive management system, supporting and inhibiting factors, as well as archivists' efforts to deal with obstacles in the archiving process at the Agriculture and Food Security Office of East Java Province. This study uses a qualitative method. The results of the study show that the archive management system at the East Java Province Agriculture and food security service uses a manual system because infrastructure and human resources are limited, in 2023 there will be a transfer to using a digital system. The supporting factor is due to the spirit of high dedication to the duties of the archivists in the archival unit. The obstacles are due to the lack of leadership support, lack of human resources regarding archives, lack of facilities and infrastructure. Efforts to deal with obstacles, namely coordination with the head of the archive and the creator unit, using the appropriate infrastructure